2021
DOI: 10.1038/s41389-021-00308-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bruton’s tyrosine kinase as a therapeutic strategy for chemoresistant oral squamous cell carcinoma and potential suppression of cancer stemness

Abstract: Locally advanced oral squamous cell carcinoma (OSCC) requires multimodal therapy, including surgery and concurrent chemoradiotherapy (CCRT). CCRT-resistant and recurrent cancer has a poor prognosis. We investigated the effects of Bruton’s tyrosine kinase (BTK) on CCRT-resistant OSCC tissues. The effect of ibrutinib, a first-in-class BTK inhibitor, was tested on stem cell-like OSCC tumorspheres. A tissue array was constructed using tissue samples from 70 patients with OSCC. Human OSCC cell lines, SAS, TW2.6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…We studied the expression of BTK in pan-cancer and adjacent tissues or normal tissues in data from 33 cancer types from TCGA database. We observed elevated expression of BTK in BRCA [49], CHOL, GBM [50], HNSC [51], KICH, KIRC [52] and KIRP, while lower expression was observed in BLCA, COAD, LUAD, LUSC, PAAD and READ. We also found that BTK expression was associated with the clinical stage of 10 types of cancers, including ACC, BLCA, ESCA, KICH, KIRP, LUAD, SKCM, STAD, TGCT and THCA.…”
Section: Discussionmentioning
confidence: 99%
“…We studied the expression of BTK in pan-cancer and adjacent tissues or normal tissues in data from 33 cancer types from TCGA database. We observed elevated expression of BTK in BRCA [49], CHOL, GBM [50], HNSC [51], KICH, KIRC [52] and KIRP, while lower expression was observed in BLCA, COAD, LUAD, LUSC, PAAD and READ. We also found that BTK expression was associated with the clinical stage of 10 types of cancers, including ACC, BLCA, ESCA, KICH, KIRP, LUAD, SKCM, STAD, TGCT and THCA.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of PI3K inhibitor, BKM-120, with TPF decreased the expression and phosphorylation of stathmin, and induced cell cycle arrest, thereby increasing the proportion of apoptotic tumor cells and inhibiting the growth of xenografts (169). The combination of Bruton's tyrosine kinase (BTK) inhibitors, ibrutinib, and cisplatin were capable of suppressing stemness characteristics and promoting apoptosis in OSCC cells (170).…”
Section: Combination With Molecular Targeted Agentsmentioning
confidence: 99%
“…These include both direct tumoricidal activities on cancer cells and indirect immunomodulatory effects on different immune cell subsets as well as other relevant cell types in the tumor microenvironment (TME) via on-target inhibition of BTK (for both drugs) or off-target inhibition of ITK or EGFR (for ibrutinib) (2, 24, 28, 29). Ibrutinib and acalabrutinib exhibit direct tumoricidal activities on certain types of solid tumor cells, including neuroblastoma, glioblastoma, breast cancer, prostate cancer, bladder cancer and advanced oral squamous cell carcinoma (OSCC) (30,31,78,(80)(81)(82). Accumulating studies report that BTK is highly expressed in certain solid tumor cells and increased BTK levels are associated with a poor prognosis in patients (30,31,78,(80)(81)(82).…”
Section: Hematological Malignancies Of Myeloid Cells and T Cellsmentioning
confidence: 99%
“…Ibrutinib and acalabrutinib exhibit direct tumoricidal activities on certain types of solid tumor cells, including neuroblastoma, glioblastoma, breast cancer, prostate cancer, bladder cancer and advanced oral squamous cell carcinoma (OSCC) (30,31,78,(80)(81)(82). Accumulating studies report that BTK is highly expressed in certain solid tumor cells and increased BTK levels are associated with a poor prognosis in patients (30,31,78,(80)(81)(82). Gene silencing of BTK or inhibition of BTK with ibrutinib or acalabrutinib attenuates the proliferation, migration, invasion and stemness of these cancer cells both in vitro and in vivo (30,31,78,(80)(81)(82).…”
Section: Hematological Malignancies Of Myeloid Cells and T Cellsmentioning
confidence: 99%
See 1 more Smart Citation